The characterization of OfRGA in regulation of flower size through tuning cell expansion genes - Wan, Qianqian; Lu, Mei; Jiang, Gege; Shao, Jiexin; Chen, Tao; Yang, Liyuan; Khan, Irshad Ahmad; Deng, Jinping; Zhong, Shiwei; Wang, Yiguang; Xiao, Zheng; Fang, Qiu; et al. (Frontiers in Plant Science, 2024)
Flower appearance stands as a key characteristic of flowering plants and is closely linked to their ornamental value. Phytohormone Gibberellin (GA), essential for plant growth and development are widely reported for expansion in flower. DELLA proteins are known to negatively regulate GA signaling and influences plant growth and development through the regulation of cell expansion. However, the specific biological function of DELLA proteins in the woody plant Osmanthus fragrans remains unclear. In this study, O. fragrans ‘Sijigui’ was utilized as the experimental material, and OfRGA was isolated using the PCR method. OfRGA is expressed in various tissues and is localized in the nucleus. A negative association was observed between OfRGA expression and petal size across four different Osmanthus fragrans cultivars. Transformation experiments in tobacco revealed that transgenic plants overexpressing OfRGA exhibited increased plant height, greater node spacing, shorter leaf length, and wider leaves during the vegetative phase. Notably, the flower organs of transgenic tobacco plants displayed noticeable alterations, including reduced petal size, shorter corolla tubes, pedicels, male and female stamens, and lighter petal color. Furthermore, a decrease in the length and area of petal and corolla tube cells was observed as well. DEGs were found in RNA-seq studies of OfRGA transgenic plants. Subsequent investigation revealed a considerable quantity of down-regulated genes were associated with cell wall synthesis genes and expansion genes, such as CesA1, XEH, and EXPB1, as well as genes related to anthocyanin biosynthesis. Overall, our findings suggest that OfRGA undermines tobacco petal size by influencing cell expansion. The present study offers a fundamental comprehension of the role of DELLA protein in the organ development in Osmanthus fragrans.